Understanding the Legal Politics of Regional Tax Regulations: Navigating Regional Autonomy in Post-Tax Reform in Indonesia - Pamuji, Kadar; Dharmawan, Aditya Riza; Kartono, Kartono; Masum, Ahmad (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2025)
This research addresses the urgent changes following the repeal of Law no. 28 of 2009, which governed Regional Taxes and Regional Levies, as incorporated into the Financial Relations between the Central Government and Local Governments Law (Law No. 1 of 2022). The repeal brings forth significant consequences, particularly affecting the authority of regional governments to shape their tax policies. To understand these impacts, we delve into the evolution of regional tax regulations in Indonesia. The legal landscape surrounding regional tax law under the HKPD Law presents a fascinating area of study. Our aim is to explore the legal politics that influence local tax management within the framework of regional autonomy in Indonesia. This study employs a normative juridical approach, utilizing various data collection methods, including interviews, focus group discussions (FGDs), and document analysis. Throughout the research, data processing and analysis occur continually as new information emerges. Our findings indicate a notable shift in legal politics surrounding local tax management in Indonesia. Current regional tax policies are increasingly designed to enhance local revenue, supporting regional autonomy while aligning with the central government’s fiscal harmonization goals. This approach aims to optimize public services and ensure the sustainability of fiscal framework.